The Impact of Digital Technology on the Implementation of Islamic Religious Education Curriculum: A Literature Review based on Research in Finland - Fadila Rahmah; Agus Pahrudin; Agus Jatmiko; Koderi (Bulletin of Science Education, 2024)
The development of digital technology has transformed various aspects of life, including education. The Islamic Religious Education (PAI) curriculum faces significant challenges in adapting to the digital era, particularly in terms of content delivery and learning methodologies. This study employs the library research method, referring to research conducted by Saarinen, Aino I. L. (2021), Digital Technology and its Impact on Education: A Study in Finland, to examine how digital technology affects education and its implications for PAI. The research analyzes the impact of digital technology on the quality of education and formulates solutions that can be applied in the implementation of the PAI curriculum. The findings show that digital technology offers significant opportunities to enhance the effectiveness of PAI learning, but also presents challenges such as a decline in scientific literacy, reading literacy, and collaborative skills. This study serves as a reference for educators and policymakers to continuously develop and support innovations relevant to the evolving times in the PAI curriculum. Keywords: Digital Technology, Islamic Religious Education Curriculum,  Finland Curriculum